George's secret key to the universe - Hawking, Lucy; Hawking, Stephen; Galfard, Christophe; Parsons, Garry (New York : Simon & Schuster Books for Young Readers, 2007)
A young boy named George discovers a powerful computer that opens a portal to explore the universe, leading him on a science-filled adventure about space, planets, and black holes.
Keywords: Science fiction; Space and time -- Juvenile fiction; Astronomy -- Juvenile fiction